Animal models for pelvic organ prolapse: systematic review - Mori da Cunha, Marina Gabriela M C; Mackova, Katerina; Hympanova, Lucie Hajkova; Bortolini, Maria Augusta T; Deprest, Jan (International urogynecology journal, 2021)
INTRODUCTION AND HYPOTHESIS: We aimed to summarize the knowledge on the pathogenesis of pelvic organ prolapse (POP) generated in animal models. METHODS: We searched MEDLINE, Embase, Cochrane and the Web of Science to establish what animal models are used in the study of suggested risk factors for the development of POP, including pregnancy, labor, delivery, parity, aging and menopause. Lack of methodologic uniformity precluded meta-analysis; hence, results are presented as a narrative review. RESULTS: A total of 7426 studies were identified, of which 51 were included in the analysis. Pregnancy has a measurable and consistent effect across species. In rats, simulated vaginal delivery induces structural changes in the pelvic floor, without complete recovery of the vaginal muscular layer and its microvasculature, though it does not induce POP. In sheep, first vaginal delivery has a measurable effect on vaginal compliance; measured effects of additional deliveries are inconsistent. Squirrel monkeys can develop POP. Denervation of their levator ani muscle facilitates this process in animals that delivered vaginally. The models used do not develop spontaneous menopause, so it is induced by ovariectomy. Effects of menopause depend on the age at ovariectomy and the interval to measurement. In several species menopause is associated with an increase in collagen content in the longer term. In rodents there were no measurable effects of age apart of elastin changes. We found no usable data for other species. CONCLUSION: In several species there are measurable effects of pregnancy, delivery and iatrogenic menopause. Squirrel monkeys can develop spontaneous prolapse.
Keywords: Sheep; Pregnancy; Menopause; Female; pánevní dno; krysa rodu Rattus; modely u zvířat; zvířata; Pathophysiology; parita; Pelvic Floor; ženské pohlaví; vedení porodu; Delivery, Obstetric; Parity; těhotenství; Models, Animal; Rats; prolaps pánevních orgánů; Ovariectomy; Age; Animals; Pelvic Organ Prolapse; ovce